Development of a High-Throughput Fluorescence Polarization Assay to Detect Inhibitors of the FAK–Paxillin Interaction. (January 2020) - Marlowe, Timothy; Alvarado, Carlos; Rivera, Andrew; Lenzo, Felicia; Nott, Rohini; Bondugji, Dena; Montoya, Justin; Hurley, Alana; Kaplan, Matt; Capaldi, Andrew; Cance, William
Focal adhesion kinase (FAK) is a promising cancer drug target due to its massive overexpression in multiple solid tumors and its critical role in the integration of signals that control proliferation, invasion, apoptosis, and metastasis. Previous FAK drug discovery and high-throughput screening have exclusively focused on the identification of inhibitors that target the kinase domain of FAK. Because FAK is both a kinase and scaffolding protein, the development of novel screening assays that detect inhibitors of FAK protein–protein interactions remains a critical need. In this report, we describe the development of a high-throughput fluorescence polarization (FP) screening assay that measures the interactions between FAK and paxillin, a focal adhesion–associated protein. We designed a tetramethylrhodamine (TAMRA)-tagged paxillin peptide based on the paxillin LD2 motif that binds to the focal adhesion targeting (FAT) domain with significant dynamic range, specificity, variability, stability, and a Z'-factor suitable for high-throughput screening. In addition, we performed a pilot screen of 1593 compounds using this FP assay, showing its feasibility for high-throughput drug screening. Finally, we identified three compounds that show dose-dependent competition of FAT–paxillin binding. This assay represents the first described high-throughput screening assay for FAK scaffold inhibitors and can accelerate drug discovery efforts for this promising drug target.